Climate change resilience in Phallusia nigra: a comparative study of native and introduced populations - Unger, Amit; Lee, Serina Siew Chen; Teo, Serena Lay Ming; Levy, Ofir; Shenkar, Noa (Frontiers in Marine Science, 2025)
Marine biological invasions, driven by climate change and maritime transportation, threaten biodiversity by reducing species richness and altering their distribution. Global efforts to understand the physiological tolerance and limitations of invasive species are essential for predicting their spread and mitigating negative impacts. Ascidians (Chordata, Ascidiacea) are well-known as notorious invaders, spreading via ship hulls, and causing significant ecological and economic damage. Environmental changes are likely to accelerate their expansion, further challenging marine ecosystems. We examined the physiological responses of native (Red Sea) and non-indigenous populations (Mediterranean and South China Sea) of a widely-distributed solitary ascidian, Phallusia nigra, to changing environmental conditions, and developed a model predicting its potential spread. Our multi-factorial design of three salinities (35, 40, 43 PSU) and three temperatures (16°C, 25°C, 31°C) examined the survivability of cultured juveniles and the reproductive success of each population. In addition, blood-flow-current change rate was used as a stress indicator. Our findings indicate survival and larval development are strongly influenced by population origin: non-indigenous populations exhibited higher tolerance to a broader range of conditions. Salinity significantly affected the Mediterranean population, whereas temperature was the primary factor for the native Red Sea population. The introduced Singapore population showed notable survival at 25° and 31°C across all salinities. Low temperatures inhibited larval development and survival across all populations, highlighting a critical reproduction barrier. Our species distribution model based on these findings predicted the potential range expansion of P. nigra under current and future climate scenarios. Responses to climate change varied among populations, however, emphasizing the need to consider local adaptations in predictive models. This study highlights P. nigra’s adaptability and demonstrates the value of species distribution models in predicting the spread of invasive species, emphasizing the need for marine biosecurity strategies to mitigate their impacts in a changing world.